2017
DOI: 10.7554/elife.28482
|View full text |Cite|
|
Sign up to set email alerts
|

A comprehensive analysis of coregulator recruitment, androgen receptor function and gene expression in prostate cancer

Abstract: Standard treatment for metastatic prostate cancer (CaP) prevents ligand-activation of androgen receptor (AR). Despite initial remission, CaP progresses while relying on AR. AR transcriptional output controls CaP behavior and is an alternative therapeutic target, but its molecular regulation is poorly understood. Here, we show that action of activated AR partitions into fractions that are controlled preferentially by different coregulators. In a 452-AR-target gene panel, each of 18 clinically relevant coregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 88 publications
(140 reference statements)
3
61
0
Order By: Relevance
“…Many AR coregulators have been described and many AR coactivators are overexpressed in primary PC and CRPC (Linja et al 2004, Heemers & Tindall 2007, Liu et al 2017. Interestingly, we showed that a number of the AR coregulators were AR regulated and that enhanced expression of a subset of these coregulators was observed in castration-challenged PC cells ectopically overexpressing AR (Urbanucci et al 2008).…”
Section: The Androgen Receptor Drives Chromatin Relaxation As An Oncomentioning
confidence: 67%
See 1 more Smart Citation
“…Many AR coregulators have been described and many AR coactivators are overexpressed in primary PC and CRPC (Linja et al 2004, Heemers & Tindall 2007, Liu et al 2017. Interestingly, we showed that a number of the AR coregulators were AR regulated and that enhanced expression of a subset of these coregulators was observed in castration-challenged PC cells ectopically overexpressing AR (Urbanucci et al 2008).…”
Section: The Androgen Receptor Drives Chromatin Relaxation As An Oncomentioning
confidence: 67%
“…The molecular events leading to the aberrant pattern of AR-binding onto chromatin in therapy-challenged PC tumors can be attributed to several interconnected factors, possibly depending on the administered intervention strategy: (i) overexpression of the AR protein that increases the abundance of the nuclear AR and the probability that the AR binds the chromatin (Jia et al 2006, Yu et al 2010, Massie et al 2011, Urbanucci et al 2012a,b, Sharma et al 2013, Stelloo et al 2015; (ii) alterations of the activity of proteins that enable binding of AR to the chromatin (pioneer factors) by triggering the recruitment of chromatin remodelers (Jia et al 2008, Lupien et al 2008, Sahu et al 2011, Robinson et al 2014, Pomerantz et al 2015; (iii) alterations in the composition of the proteins within the AR transcriptional complex which also include a number of co-regulatory proteins (Kotaja et al 2002, Heemers & Tindall 2007, Jia et al 2008, Jariwala et al 2009, Rytinki et al 2011, Liu et al 2017, Stelloo et al 2018 and (iv) alterations in the chromatin structure and composition, which renders it more permissive toward AR binding (Jia et al 2006, Yu et al 2010, Andreu-Vieyra et al 2011, Tewari et al 2012, Stelloo et al 2015.…”
Section: The Androgen Receptor Drives Chromatin Relaxation As An Oncomentioning
confidence: 99%
“…The second most common subtype (MetB) shows poor prognosis after ADT and some features similar to neuroendocrine tumors, such as high cell cycle activity and DNA damage (Flores-Morales et al, 2019), but as chromogranin expression is generally low and KRT18 and AR expression retained, we suggest that MetB shows a dedifferentiated luminal phenotype. The contrasting processes of cell differentiation and proliferation are both driven by androgens in the prostate (Cai et al, 2011;Gao et al, 2016;Yang et al, 2016), but in a context-dependent way that seems reprogrammed during cancer progression by coactivators and corepressors modulating the AR cistrome (Sharma et al, 2013;Liu et al, 2017). AR activation in the presence of coactivator FOXA1 results in cell differentiation, PSA secretion, and suppressed proliferation (Cai et al, 2011;Gao et al, 2003Gao et al, , 2016Yang et al, 2016), while in cells with low FOXA1, this instead stimulates cell proliferation (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that therapeutic targeting will be improved in the future because of an increased number of patient-derived xenografts [14]. It is therefore possible that improved methodologies in laboratory diagnostics will lead to establishment of analytical methods for investigation of a larger number of coactivators that are overexpressed in prostate cancer [15]. Although most studies have focused on coactivators, it should be mentioned that corepressors such as REST may be inactivated in the disease [16].…”
Section: Clinically Relevant Ar Coactivatorsmentioning
confidence: 99%